Reference Note on Trade Policy, Preferential Trade Agreements, and WTO Consistency. (Policy Papers; Policy Paper ;, 2010)
This Reference Note introduces guidance on preferential trade agreements (PTAs). In so doing, it responds to the request by the Executive Board in the context of the Independent Evaluation Office (IEO) Evaluation of IMF Involvement in Trade Policy Issues. Section II provides context for the Fund's work on trade policy, drawing upon the 2009 IEO Evaluation, the 2005 Review of Fund Work on Trade, and the discussion of the Executive Board on these occasions. Section III reflects issues presented in Preferential Trade Agreements-Issues for the Fund, discussed at an informal Board seminar in December 2006.